Evaluation of soil liquefaction in the city of Hatay triggered after the February 6, 2023 Kahramanmaras,-Türkiye earthquake sequence - Bol, Ertan; Ozocak, Askin; Sert, Sedat; Cetin, Kemal Onder; Arslan, Eylem; Kocaman, Kadir; Ayhan, Bilal Umut (Elsevier, 2024)
This study investigates the consequences of consequences of liquefaction hazards following the February 6, 2023, Kahramanmaras, Earthquakes in Hatay, T & uuml;rkiye. Field reconnaissance surveys were conducted in areas prone to liquefaction, including recent alluvial basins, the Amik (Amuq) Plain, and the Asi (Orontes) River. Specifically, attention was given to I(center dot)skenderun (Alexandretta), Dortyol coasts, the Hatay Airport region, and Demirkopr & uuml; village near the Asi River. Observations indicated that geological and geomorphological factors primarily influenced liquefaction ejecta and liquefaction-induced lateral spreading in these areas. In Dortyol, liquefaction manifestations were observed on the coastline, which has undergone natural processes, while in I(center dot)skenderun, they occurred on human-made extended reclaimed land. Additionally, liquefaction manifestations in the Hatay Airport region were impacted by the drained Amik Lake, and those in Demirkopr & uuml; Village were influenced by the fluvial nature of the Asi River and its sub facies. The sites experiencing liquefaction and lateral spreading mainly comprised coastal deposits, lacustrine sediments, and sub facies of the meandering river, such as point bars, abandoned channels, and levees. Consequently, the study underscores the significant correlation between geomorphology and liquefaction hazards in the context of the 2023 Kahramanmaras,-T & uuml;rkiye Earthquakes. Considering these factors may facilitate further research and the identification of sites susceptible to liquefaction.
Keywords: Soil Liquefaction; Lateral Spreading; Geomorphological Features; Hatay; 2023 Kahramanmaras; T & Uuml;Rkiye Earthquakes